Case Report: Gastric Carcinoma Diagnosed at the Second Trimester of Pregnancy - Tayfur Cift; Begüm Aydogan; Murat Akbaş; Burcu Aydın; Fuat Demirkiran; Dogu V. Bakkaloglu; Sennur Ilvan (Case Reports in Obstetrics and Gynecology)
We report a rare case of gastric cancer in pregnancy. A 26-year-old woman presented at the 20th week of pregnancy complaining of nausea and vomiting. Although the patient considered the condition to be related with pregnancy and underestimated its importance, her complaints persisted over the following weeks and she was hospitalized for investigation. The diagnostic workup revealed a metastatic gastric cancer. Gastric cancer is very rare in pregnancy, and therefore it may be left out of differential diagnosis by physicians. Diagnosis may be further delayed because of overlapping symptoms occurring during normal pregnancy (nausea, vomiting, and fatigue). All these factors may contribute to a very high mortality of this malignancy during pregnancy.